Flipping Your English Class to Reach All Learners : Strategies and Lesson Plans. - Cockrum, Troy (Taylor and Francis, 2013)
Learn how flipping your English language arts classroom can help you reach students of different abilities, improve classroom management, and give you more time to interact with each student. This practical book shows why flipped classrooms are effective and how they work. You will find out how to flip your instruction in writing, reading, language, and speaking and listening while meeting the Common Core State Standards. A variety of step-by-step lesson plans are provided.